PROTOTIPE INSTALASI PENGOLAHAN AIR LIMBAH INDUSTRI PENGOLAHAN IKAN DI KECAMATAN MUNCAR, KABUPATEN BANYUWANGI - ., Setiyono; Yudo, Satmoko (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Muncar region known as the area of the fish and the fish processing industry. ManyÃ‚Â of the fish processing industries in large scale, small scale and household at this timeÃ‚Â growing so rapidly. With the rapid growth of the fish processing industry in the MuncarÃ‚Â city has provided a very significant impact on the city growth, which eventually broughtÃ‚Â the various impacts, whether they are positive or negative. One of the negative impactÃ‚Â of processing industry growth in Muncar is environmental of pollution is the dischargeÃ‚Â of liquid waste from industrial fish-processing industry. Low level of understanding IPALÃ‚Â waste management system and cause difficulties to manage the waste, therefore almostall waste that generated in the region immediately removed to the public channels.Ã‚Â Waste disposal without treatment is causing high level of environmental pollution in theÃ‚Â vicinity of the location of industry. One effort to solve the problem of waste-processing technology is determine processingof waste water and fish processing, it has been done to test prototype installationÃ‚Â processing waste water in one of the fish processing industry in the Muncar District.Ã‚Â Key words : fish processing industry waste water, environmetal pollution, waste waterÃ‚Â processing prototype.